Tiban Market and Utilization of Public Areas in the Maqasid Syari'ah Perspective: Perception of Islamic Scholars and Traders - Hidayah, Alfi (Universitas Islam Negeri K.H. Abdurrahman Wahid Pekalongan, 2018)
The utilization of state-owned public areas is widespread in various places, not only locally but also nationally. This research examines critically the use of public areas by tiban market traders for the purpose of trading in Warungasem District, Batang Regency, Central Java, Indonesia. In addition, this study explores the perceptions of Islamic scholars (ulama), traders and the government on the use of public areas as trade locations. Public land use is examined through qualitative research, with data collection techniques: interviews, observation and documentation, and analyzed with interactive models. This study finds that trading on the highway is actually not permitted by regulation. Both traders and the government have the same point of understanding. Traders continue to use highways as stalls solely to fulfill clothing, shelter and food needs, because they do not own land. Meanwhile, the scholar's perception of the use of the public arena is polarized into two, which is permissible and not. For those who allow it, the existence of the tiban market is considered to have more benefits than dangers. On the contrary, by referring to the maqasid syari'ah, the scholars allow on the grounds of the tiban market have fundamental benefits both economically, socially and can prosper the people, in the midst of the country which is less concerned with the growth of economic populism.